Laparoscopic Management of a Giant Paratubal Cyst: A Case Report - Khan, Sadia; Batool, Ismat; Naheed, Nighat; Saleem, Hina; Kanwal, Arshia; Javed, Ayesha (Journal of Rawalpindi Medical College, 2026)
Large paratubal cysts are uncommon benign adnexal lesions that can closely resemble ovarian cysts on both clinical and radiologic assessment. Their laparoscopic excision can be technically demanding, particularly when fertility preservation is desired. We describe a 24-year-old woman who presented with gradually increasing abdominal distension and right lower abdominal pain. Imaging revealed a 25 × 15 × 10 cm right-sided adnexal cyst with the ovary draped over its surface, suggesting a paratubal origin. All tumor markers were within normal limits. Laparoscopic cystectomy with controlled decompression was carried out, and all pelvic organs were preserved. Histopathology confirmed a benign paratubal cyst. The postoperative course was smooth, and the patient was discharged the next day. This case demonstrates that, with careful preoperative evaluation and meticulous surgical technique, laparoscopy can be safely and effectively used even for very large paratubal cysts. Keywords: Paratubal cyst, Broad ligament cyst, Laparoscopic cystectomy, Giant adnexal mass, Fertility preservation.